Investment analysis and portfolio management - Reilly, Frank K. (Thomson/South-Western, 2006)
The purpose of this text is to help the student learn how to manage their money to derive the maximum benefit from what they earn. Mixing investment instruments and capital markets with the theoretical detail on evaluating investments and opportunities to satisfy risk-return objectives along with how investment practice and theory is influenced by globalization. The material is intended to be rigorous and empirical yet not overly quantitative. Reilly/Brown provides the best foundation, used extensively by professionals, organizations, and schools across the country. A great source for those with both a theoretical and practical need for investment expertise.